DNA Damage, Defective DNA Repair, and Neurodegeneration in Amyotrophic Lateral Sclerosis - Konopka, Anna; Atkin, Julie D. (Frontiers in Aging Neuroscience, 2022)
DNA is under constant attack from both endogenous and exogenous sources, and when damaged, specific cellular signalling pathways respond, collectively termed the ‘DNA damage response’. Efficient DNA repair processes are essential for cellular viability, although they decline significantly during aging. Not surprisingly, DNA damage and defective DNA repair are now increasingly implicated in age-related neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). ALS affects both upper and lower motor neurons in the brain, brainstem and spinal cord, leading to muscle wasting due to denervation. DNA damage is increasingly implicated in the pathophysiology of ALS, and interestingly, the number of DNA damage or repair proteins linked to ALS is steadily growing. This includes TAR DNA binding protein 43 (TDP-43), a DNA/RNA binding protein that is present in a pathological form in almost all (97%) cases of ALS. Hence TDP-43 pathology is central to neurodegeneration in this condition. Fused In Sarcoma bears structural and functional similarities to TDP-43 and it also functions in DNA repair. Chromosome 9 open reading frame 72 (C9orf72) is also fundamental to ALS because mutations in C9orf72 are the most frequent genetic cause of both ALS and related condition frontotemporal dementia (FTD), at least in European and North American populations. Genetic variants encoding other proteins involved in the DNA damage response have also been described in ALS, including FUS, SOD1, SETX, VCP, CCNF, and NEK1. Here we review recent evidence highlighting DNA damage and defective DNA repair as an important mechanism linked to neurodegeneration in ALS.